Early developmental changes in GABAA receptor expression in nucleus accumbens medium spiny neurons - Wang, Ziyi (Zephyr); Folorunso, Oluwarotimi O.; Morris, Kiely; Berretta, Sabina; Engin, Elif (Frontiers in Neuroscience, 2024)
The expression of GABAARs goes through large scale, evolutionarily conserved changes through the early postnatal period. While these changes have been well-studied in brain regions such as the hippocampus and sensory cortices, less is known about early developmental changes in other brain areas. The nucleus accumbens (NAc) is a major hub in the circuitry that mediates motivated behaviors and disruptions in NAc activity is a part of the neuropathology observed in mood and substance use disorders. Considering the importance of early developmental disruptions in the vulnerability to and etiology of these disorders, it is essential to understand normal developmental changes in the NAc as a first step to understanding how these changes might be disrupted to cause long-term pathology. Here, we aimed to address the gap in knowledge of early developmental changes in GABAAR expression in NAc neurons. We investigated the expression patterns of GABAAR α1, α2, and α4 subunits in Drd1+, Drd2+, and putative hybrid medium spiny neurons (MSNs) of the mouse NAc over a developmental window from P2 to P16. Our findings show a consistent increase in expression of all 3 GABAAR subunits in Drd1+ MSNs, accompanied by stable expression or even a decrease in expression in Drd2+ MSNs. The putative hybrid population showed a complex expression pattern, usually showing maximum expression at P9. These early developmental changes likely suggest a specific window where GABAAR expression patterns adjust to increasing glutamatergic inputs from external sources, changes in intracellular chloride concentrations, and a switch towards the mature, bistable activity patterns of MSNs from the immature, relatively excitable singular pattern. We propose that this time of dynamic changes in GABAAR expression could represent a sensitive period during which developmental insults might lead to permanent disruptions in GABAAR expression patterns.